Helicobacter pylori-negative Gastric Cancer - Jin Seok Jang (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2017)
Although Helicobacter pylori is considered the main etiological factor in gastric cancer, at least 5.4% of gastric cancer cases in South Korean patients are H. pylori-negative. However, false-negative H. pylori results should be considered. The definitions of H. pylori status in patients with atrophic gastritis but negative tests for H. pylori are variable. Inaccurate H. pylori detection systems can interfere with interpretation of the results. Even when H. pylori has been eradicated, gastric atrophy and intestinal metaplasia resulting from long-term colonization can occur. It is very difficult to determine whether patients with gastric cancer, who frequently have advanced gastric atrophy and intestinal metaplasia, have had previous H. pylori infection based on invasive tests. In addition, H. pylori-negative gastric cancers present with a more advanced pT classification and a more advanced stage than H. pylori-positive gastric cancers. Negative H. pylori status appears to be an indicator of poor prognosis in patients with gastric cancer, and is independent of other well-known clinical and pathologic prognostic variables.